(untitled) (CAHIERS MAGELLANES-NS, 2024)
IoT devices are resource-constrained in terms of processing, storage, and networking capacity, which makes it a difficult task to secure access to them. Today's authentication and access control schemes exhibit substantial drawbacks as a result of their rapid dissemination and implementation. This paper suggests a blockchain-based solution that enables secure communication and authentication with IoT devices. Our solution capitalizes on the inherent characteristics of blockchain technology and augments existing authentication protocols. Specifically, our proposed blockchain-based solution, architecture, and design enable accountability, integrity, and traceability through tamper-proof logs. The paper offers a comprehensive overview of the system's design and architecture, as well as specifics regarding the testing and implementation of a realistic scenario as a proof of concept.